PERSEPSI KEMUDAHAN DAN PERILAKU PEMBELIAN IMPULSIF PADA LAYANAN BUY NOW PAY LATER: PERAN MEDIASI MOTIVASI BELANJA HEDONIS DAN PERAN MODERATOR KONTROL DIRI: (PERCEIVED EASE OF USE AND IMPULSIVE BUYING IN BUY NOW PAY LATER SERVICE: THE MEDIATING ROLE OF HEDONIC SHOPPING MOTIVATION AND THE MODERATING ROLE OF SELF-CONTROL) - Widyastuti, Liza Yudhita; Azzahra, Yulia Chaerani; Izzah, Khalid Ahmad; Rein, Sasikirana; Rustyawati, Reny; Putri, Fildzah Rudyah (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study is the first research which empirically examine the psychological mechanism of impulsive buying among Buy Now Pay Later (BNPL) users, specifically Shopee PayLater. The mechanism consists the influence of perceived ease of use of Shopee PayLater on impulsive buying, mediated by hedonic shopping motivation and moderated by self-control. Data from 301 Shopee PayLater users were analyzed using Hayes PROCESS Macro in SPSS. This study indicate that perceived ease of use significantly predicts hedonic shopping motivation. Although its direct contribution is small (R2 = 0.029), the indirect effect on impulsive buying is sufficient to stimulate the affective aspect (hedonic shopping motivation) that drives impulsive buying in the BNPL ecosystem. Notably, this mediated effect remained significant even among individuals with high self-control (indirect effect = 0.171; 95% CI = 0.024–0.373). Thus, while self-control moderates and weakens the relationship between hedonic shopping motivation and impulsive buying, its effect is limited. Researcher suggest additional variables which are capable to suppress impulsivity and to foster healthier and more responsible consumption behavior. These findings contribute to create digital financial literacy education and propose ethical design BNPL service.